Harnessing Natural Aquifer Filtration for Large-Scale Water Purification: Opportunities and Challenges - Kumar S Vinod; Kumar Jayasheel; Lakhanpal Sorabh; Yadav Dinesh Kumar; Sharma Shekhar; Abood Ahmed Salam (E3S Web of Conferences, 2024)
The research investigates the potential benefits of utilizing natural aquifer systems as a means of water treatment on an extensive basis. The present study analyzes the mechanisms via which naturally aquifers properly filter water, examining the possibilities to be practical financially effective ways for dealing with the growing demand for safe water. The paper highlights the potential advantages associated with natural aquifers filtration, such as its small environmental impact and its ability to sustain water quality. At the same time, it recognizes the challenges that have to be overcome, including the risk of pollution, the complex nature of laws and regulations, and the necessity of successfully controlling aquifer recharge. This study incorporates many geological, hydrological, and ecological engineering perspectives in order to offer an in-depth study of natural aquifer filter systems. This study aims to examine case studies and present practices in order to provide an in-depth strategy for effective use of these systems in various global environments. It also takes into consideration the significant potential of these mechanisms as well as the obstacles that need to be solved.